Politik pendidikan: Respons kebijakan desentralisasi dalam penyelenggaraan urusan pendidikan menengah di Kota Surabaya - Indra Widyanto (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2022)
Research done by looking at the phenomena that occur in the process of handover Affairs organizing equal high school education from City Government to the provincial government. Act No. 23-year 2014 about local government that has been in effect became the legal basis for the change of venue secondary education affairs. Changes to this affair had a chance to get a rejection from the head area of the city/county level, one of which the city of Surabaya. Qualitative research-descriptive using the theory of decentralization. The purpose of change the organization of the education is done so that each level of Government has a particular focus in the field of education. In the process of the transition of the Organization of the secondary education reap the response of the Government of the city of Surabaya and East Java provincial government. Changes made in adjusting the policy of decentralization that is created. The results of these studies gave rise to the implications of changes in the organization of secondary education. The policy of decentralization provide implications on educators, budget, and social.